Simplifying Treatment Criteria in Chronic Hepatitis B: Reducing Barriers to Elimination. (20th May 2022) - Wong, Robert J; Kaufman, Harvey W; Niles, Justin K; Kapoor, Hema; Gish, Robert G
Abstract: Background: Early, sustained hepatitis B virus (HBV) DNA suppression reduces long-term risks of hepatocellular carcinoma. Chronic hepatitis B (CHB) treatment criteria are complex. Simplifying criteria will improve timely linkage to therapy. We evaluated treatment eligibility patterns among US patients with CHB and propose stepwise simplification of CHB treatment criteria. Methods: Using 2016–2020 Quest Diagnostics data, we evaluated treatment eligibility among patients with CHB (2 positive HBV tests [HBV surface antigen, HBV e antigen, or HBV DNA] ≥6 months apart) using American Association for the Study of Liver Disease (AASLD), European Association for Study of the Liver (EASL), Asian Pacific Association for Study of the Liver (APASL), and Asian American Treatment Algorithm (AATA) criteria. Results: Among 84 916 patients with CHB, 6.7%, 6.2%, 5.8%, and 16.4% met AASLD, EASL, APASL, and AATA criteria, respectively. Among treatment-ineligible patients with CHB, proportion with significant fibrosis (aspartate aminotransferase platelet ratio index >0.5) were 10.4%, 10.4%, 10.8%, and 7.7% based on AASLD, EASL, APASL, and AATA, respectively. In the proposed treatment simplification, the proportion of patients with CHB eligible for therapy increased from 10.3% for step 1 (HBV DNA >20 000 IU/mL, elevated alanine aminotransferase [ALT] level) to 14.1% for step 2 (HBV >2000 IU/mL, elevated ALT level), 33.5% for step 3 (HBV DNA >2000 IU/mL, any ALT level), and 87.2% for step 4 (detectable HBV DNA, any ALT level). Conclusions: A large proportion of patients with CHB not meeting established treatment criteria have significant fibrosis. Simplifying criteria to treat all patients with detectable HBV DNA will reduce complexity and heterogeneity in assessing treatment eligibility, improving treatment rates and progress toward HBV elimination. Abstract : Current treatment eligibility algorithms for chronic hepatitis B are complex and may contribute to missed opportunities for early antiviral therapy. Using a large US laboratory database, we propose a stepwise simplification of chronic hepatitis B treatment eligibility to be considered.